KOORDİNASYON BİLEŞİKLERİNİN ARABASAMAK VE TOPLAM KARARLILIK SABİTLERİNİN POTANSİYOMETRİK YÖNTEMLE TAYİNİ - KAYA, FATMA (Fırat Üniveristesi, 2001)
In this work, to calculate the stepwise and overall stability constants of coordination compounds from potentiometric titration data, a computer program have been written. The computer program runs under Windows operating system and written for symbolic programming language, MathCad, which utilizes Newton-Raphson method for solving the non-linear equations. The computer program was tested with potentiometer titration data from Ni(II)glycine and Cu(II)glycine complexes. It was found that the stability constant we found from the experimental data and literatures were in good agreement with each other. After seeing that the computer program works well with the data we get from method, it was applied to the two ethanol amine complexes of Co(III) and Cr(III). The the potentiometric titration stability constants of both complexes were calculated as 1.51 and 70.5 respectively. Key Words: Potentiometric titration^ stepwise stability constant, overall stability constant, nickel, cupper, cobalt, chrome, complex, non-linear, MathCad. Ill
Determination of stability and formation constant of metal complexes by potentiometric titration
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Kimya; Chemistry